Description of Cadres' Knowledge and Attitudes Towards Massage Therapy in Increasing Body Weight in Stunted Toddlers in Tanjung Riau Village, Batam City - Putri, Hariyanda; Laska, Yulinda; Mastikana, Indah; Hariyati, Shapna Lina (Future Science, 2024)
Stunting is one of the focuses of nutrition improvement target in the world until 2025. The incidence of Stunting is an impact from insufficient nutritional intake both in terms of quality and quantity, highly of health, or the impact from both. The purpose of this study to know description of knowledge and attitude towards massage therapy to increase weight on stunting toddlers. In research use quantitive research with design one group pre-test post-test, the sample of research use voluntary sampling has done in 6 Integrated Health Post (ITH) at Tanjung Riau Area in Batam City, total sample is 42 respondents. The results of the research is the most of the respondents who have a good knowledge about massage therapy to increase weight on stunting toddlers as many as 14 respondents (33,5%), and very good attitude about massage therapy to increase weight on stunting toddlers as many as 16 respondents (38%). Advice for cadres that should improve about knowledge and attitude towards massage therapy to increasing weight on stunting toddlers.